(untitled) (Journal of Comparative Social Work, 2016)
Background: One common arrangement in the Norwegian child welfare system is the interprofessional collaborating team, not unlike the English core group. This team is often referred to as the ‘responsible team’ (RT) and is arranged when a child has needs that call for several services. Few studies about interprofessional collaboration focus on views of service users and, in particular, those of child and adolescent service users. Aims and objectives: The present study aims to explore adolescents’ subjective views about their participation in RTs. This study contributes further knowledge about the field of interprofessional collaboration, especially regarding the participation of adolescents. Design: Non-experimental, exploratory research design. Methods: Q-methodology was used to explore 26 adolescents’ subjective views about their collaboration within the responsible teams that were formed to support their welfare. Q-methodology is known as being particularly suitable for revealing vulnerable people’s nuanced subjective views and perspectives. The adolescents in this study were asked to rank order a set of 42 statements (Q-set). PQMethod was used to analyse the data. Results: Four factors emerged and revealed patterns of shared views among the adolescents. Factor 1: Optimistic and engaged despite bad experiences, Factor 2: Strive to not be defeated by their helpers, Factor 3: Battle weary and resigned, and Factor 4: Content, positive and full of trust. Implications: The present study may be relevant to researchers, health and social policy makers, in addition to professionals working in services that aim to improve children’s situations through interprofessional collaboration.